CONTRIBUTION OF VALUE ADDED HUMAN CAPITAL TO EMPLOYEE PRODUCTIVITY IN CRAFT CREATIVE INDUSTRY OF TASIKMALAYA - Marlina, Lina; Sulaeman, Maman; Mundzir, A (Universitas Pamulang, 2018)
The creative industry is the focus of government to boost economic growth in recent decades. Creative industry is the utilization of talent, ideas, and creativity in generating creativity and creative power of individuals. Craft creative industry (kriya) sub-sector as a typical product of Tasikmalaya become focus of the researcher. The population of workers in the creative industries is dominated by high school graduates. It's interesting to measure the added value and productivity. This study aims to measure the contribution and influence of value added human capital (VAHU) on emplyee productivity (EP). VAHU is one component of the value added inlellectual coefficient (VAIC) Method developed by Pulic. The study focuses on VAHU because the research sphere is related to the workforce. The results of the study are expected to help creative industry entrepreneurs and decision makers to make policies related to a competent labor supplyprogram. This research uses quantitative descriptive analysis with primary and secondary data. Documentation is taken from company reports recorded in the industry and trade offices in Tasikmalaya for the last six years. Random sampling includes the creative industries of embroidery craft, footwear, furniture, batik, and mendong (wicker). The results showed that the footwear craft industry reached the highest VAHU and the lowest mendong industry. The highest EP is seen in the embroidery industry and the lowest furniture industry. While compliance between variables in this study showed that VAHU no significant effect on EP.